Designing and develop single phase transformer differential protection relay model / Faizal Mohamad Twon Tawi - Mohamad Twon Tawi, Faizal (2006)
This thesis describes a case study the operation and function of differential protection when faults occur at certain zone in transformer. The function of protection relay was to properly operate circuit breakers so as to disconnect only the faulty apparatus from the system as fast as possible. Thus, the interruption and damage can minimize when fault occur. The differential protective relay is the most widely use in protection system. (Them/ is impossible to study deeply about protection in real power system.